Handbook of Atopic Eczema - Ring, Johannes.; Ring, Johannes.; Przybilla, Bernhard.; Przybilla, Bernhard.; Ruzicka, Thomas.; Ruzicka, Thomas. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Atopic eczema (atopic dermatitis, neurodermitis diffusa, endogenous eczema) is one of the most common skin diseases of our time and is still increasing in prevalence dramatically all over the world. The reasons for this increase are not known. It occurs at any age, not only in childhood, approximately 2/3 of children affected will suffer from this disease when they are grown-up. Written by leading experts of their field, this second edition comprises the state of the art in pathophysiology, clinical medicine and therapeutic management. It demonstrates that there is no simple "miracle" cream, pill or diet for this disease, but that a disturbed barrier function can only be repaired by adequate and individualized skin care and it shows how unspecific anti-inflammatory treatment has to be individually tailored according to body area affected, patient age and acuity of skin lesions. All physicians will find this book most helpful in the painstaking search for the individual causal or eliciting factors.